Ginsenoside Rb1 Lessens Gastric Precancerous Lesions by Interfering With β-Catenin/TCF4 Interaction - Zeng, Jinhao; Ma, Xiao; Zhao, Ziyi; Chen, Yu; Wang, Jundong; Hao, Yanwei; Yu, Junrong; Zeng, Zhongzhen; Chen, Nianzhi; Zhao, Maoyuan; Tang, Jianyuan; Gong, Daoyin (Frontiers in Pharmacology, 2021)
Background: Seeking novel and effective therapies for gastric precancerous lesions (GPL) is crucial to reducing the incidence of gastric cancer. Ginsenoside Rb1 (GRb1) is a major ginsenoside in ginseng and has been proved to possess multiple bioactivities. However, whether GRb1 could protect against GPL and the underlying mechanisms have not been explored. Methods: We evaluated the effects of GRb1 on gastric precancerous lesions in rats on macroscopic, microscopic and ultramicroscopic levels. Then, an antibody array was employed to screen differential expression proteins (DEPs). Validation for the targeting DEP and investigation for the possible mechanism was conducted using immunohistochemistry, qRT-PCR, TUNEL apoptosis assay, immunoprecipitation and immunoblotting. Results: GRb1 was found to reverse intestinal metaplasia and a portion of dysplasia in the MNNG-induced GPL rats. The antibody array assay revealed seven DEPs in GPL rats as compared to control rats (5 DEPs were up-regulated, while two DEPs were down-regulated). Among the DEPs, β-catenin, beta-NGF and FSTL1 were significantly down-regulated after GRb1 administration. Our validation results revealed that enhanced protein expression and nuclear translocation of β-catenin were present in animal GPL samples. In addition, analysis of human gastric specimens demonstrated that β-catenin up-regulation and nuclear translocation were significantly associated with advanced GPL pathology. GRb1 intervention not only decreased protein expression and nuclear translocation of β-catenin, but interfered with β-catenin/TCF4 interaction. Along with this, declined transcriptional and protein expression levels of downstream target genes including c-myc, cyclin D1 and Birc5 were observed in GRb1-treated GPL rats. Conclusion: GRb1 is capable of preventing the occurrence and progression of GPL, which might be contributed by diminishing protein expression and nuclear translocation of β-catenin and interfering with β-catenin/TCF4 interaction.